Analysis of the geoecological situation in Kalush: current situation and ways of solving the problem - Zhyrnov, Pavlo; Tomchenko, Olha; Pidlisetska, Iryna; Mykolaienko, Olena (Geodesy and Cartography, 2021)
Careless economic activity of chemical and mining enterprises of the Kalush-Holyn potassium salts deposit has caused ecological disbalance in a subsurface rock layers. This caused a technogenic disaster in Kalush such as the intensification of dangerous geological processes: flooding and waterlogging of lands, intensification of karst and suffusion processes, deterioration of groundwater and surface water. The study results of the geoecological situation in Kalush using research reports’ materials of the specialized state enterprises and relevant thematic maps; and interpretation of remote sensing data are higlighted in the article. Comprehensive map of the geoecological situation of Kalush was developed in order to visualize the processes associated with the deformation of the earth’s surface in the area of Kalush and other negative phenomena that must be taken into account when planning the development of the city.